ETHICAL LEADERSHIP: MENINGKATKAN KINERJA ORGANISASI MASA PANDEMI COVID 19 - M Trihudiyatmanto (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
This study examines the effect of ethical leadership on organizational performance moderated by the COVID-19 pandemic. It seems that the COVID-19 pandemic has an important moderating role in the role of the relationship between ethical leadership and organizational performance. According to theory, organizational performance is influenced by the attitudes and decisions made by an ethical leader.The purpose of this study was to analyze how much influence ethical leadership has on organizational performance. The variables studied were the independent variable ethical leadership and the dependent variable was organizational performance with the Covid-19 pandemic as a moderating variable. The research data were obtained from Wood Industri PT. Phoenix Agung Pratama (PAP) who is domiciled in Wonosobo District, Wonosobo Regency, Central Java Province. Withdrawal of samples from the population using the census sampling method. The data were collected using a survey method, namely the questionnaire was delivered and taken directly to the research object. Data analysis used the Structural Equation Modeling (SEM) test by checking the independent variables, moderating variables and dependent variables.From the research that has been done, it is found that ethical leadership antecedents affect organizational performance at PT. PAP. Ethical leadership antecedents affect the organizational performance of the Covid-19 pandemic as a moderating variable at PT. PAP. This means that covid-19 moderates the relationship between Ethical Leadership and Organizational Performance at PT. Phoenix Agung Pratama (PAP) Wonosobo Regency